SDGs and Islamic Studies: Fiqh Muamalat, Sustainable Development, and Maqashid Asy-Syari’ah - Abdurrahman, Landy Trisna; Saifullah, Ulinnuha; Darussalam, Ishlahu; Arkham, Sitta A’la (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2022)
Sustainable development Goals (SDGs) are a form of development, or even a further form of the Millennium Development Goals (MDGs). The SDGs, which contain 17 Goals and 169 Targets, are a global action plan for the next 15 years (effective from 2016 to 2030), to end poverty, reduce inequality and protect the environment. This discourse on SDGs is a global discourse, Muslims, as a part of the global order, are also part of this discourse. In the SDGs discourse as a global discourse, the SDGs need to be studied through Islamic studies. This paper tries to portray how the SDGs are studied through Islamic studies, especially in relation to the scientific discipline of fiqh. This study is considered necessary because fiqh is often considered as something final and sacred, while the SDGs are something “new” and dynamic. This paper tries to find a meeting point between fiqh as an Islamic study, and the SDGs as a global discourse. The results in this paper show that fiqh, as a scientific discipline, also has future-oriented dimensions through empirical evidence in classical fiqh literature and empirical evidence in the form of developing a methodology for finding Islamic law (fiqh). In addition, SDGs can be proposed as the main theme for the benefit of mankind as a benchmark and measuring instrument to measure the level of achievement of Maqashid Ash-Shari'ah in the contemporary era.